A commentary and correction on the article "Pansharpening by exploiting sharpness of the spatial structure". Issue 6 (18th March 2016) - Rong, Kaixuan; Wang, Shuang; Yang, Shuyuan; Jiao, Licheng
ABSTRACT: This study clarifies the implicit potential deficiency caused by the sparse cardinality parameter k in Rong et al. (2014). In addition, k  =  β  ×  W  ×  M  ×  N (0.9 ≤  β   <  1) is suggested to avert this potential deficiency, where β is a ratio controlling the amount of sparse cardinality, W is the number of multispectral bands and M  ×  N is the size of panchromatic image. With the choice of k suggested in this study, the low rank matrixL and sparse matrixS obtained by Go Decomposition (Zhou and Tao 2011) can be iteratively optimized and solved. Thus, instead of choosing k as W  ×  M  ×  N in Rong et al. (2014), the potential deficiency thatL is directly obtained as an analytic solution can be averted.